Citrus Extract Modified Graphene Oxide as a Green and Heterogeneous Organocatalyst for the Synthesis of Imidazole Derivatives - Arunkumar, S.; Chidambara Vinayagam, S.; Lakshmanan, S.; Arul Antony, S. (Asian Journal of Chemistry, 2020)
A naturally benign convention was created with a surface change of graphene oxide by citrus extract as catalyst was prepared by a straight-forward chemical modification method. The prepared catalyst′s catalytic activity was examined by the synthesis of imidazole derivatives at room temperature. It shows a strong acidic catalytic and sustainable organocatalyst. The prepared catalyst was characterized using different analytical procedures like elemental analysis, Fourier transforms infrared spectroscopy (FT-IR), powder X-ray diffraction (PXRD), energy-dispersive X-ray analysis (EDS), scanning electron microscopy images (SEM) and transmission electron microscopy images (TEM) analysis. The catalytic activity shows high activity and can be reused without significant loss of catalytic activity after five times. A present catalyst works easily under room temperature.